2004
DOI: 10.7326/0003-4819-141-5-200409070-00106
|View full text |Cite|
|
Sign up to set email alerts
|

A Clinical Prediction Rule for Diagnosing Severe Acute Respiratory Syndrome in the Emergency Department

Abstract: Our findings suggest that a simple model that uses clinical data at the time of presentation to an emergency department during an acute outbreak predicted the incidence of SARS and provided good diagnostic utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…This higher incidence of virologic failure, coupled with the limited resources in clinical practice as compared with clinical trials, emphasizes the need for a simple prog-nostic tool to identify patients at increased risk of virologic failure. As is the case with diabetes, congestive heart failure, and other chronic diseases, a prediction rule to stratify HIV-positive patients' risk of future virologic failure could be used to target interventions and guide the allocation of resources [8][9][10][11][12].…”
mentioning
confidence: 99%
“…This higher incidence of virologic failure, coupled with the limited resources in clinical practice as compared with clinical trials, emphasizes the need for a simple prog-nostic tool to identify patients at increased risk of virologic failure. As is the case with diabetes, congestive heart failure, and other chronic diseases, a prediction rule to stratify HIV-positive patients' risk of future virologic failure could be used to target interventions and guide the allocation of resources [8][9][10][11][12].…”
mentioning
confidence: 99%
“…The scores were reported to have greater than 90% sensitivity and were found to be highly reliable when validated in a separate cohort [105,107]. A more recent study from Hong Kong, which included nearly one third of the SARS cases from 2003, reported similar results with key variables including exposure history, symptoms, and laboratory values [104]. Although determination of which prediction rule will be most effective is not known, these studies provide compelling support for integration of ED-based decision guidelines in future respiratory outbreaks.…”
Section: Secondary Prevention Measures For Sars Have Involved Methodsmentioning
confidence: 85%
“…The WHO definition of SARS cases, although useful for epidemiologic purposes, was found to be insufficiently sensitive for assessing patients in ED triage areas. Consequently, physicians had to develop clinical prediction rules that could more accurately identify patients with SARS during an acute outbreak [104][105][106][107]. One group from Taiwan derived a simple SARS decision rule that relied on combinations of symptoms and laboratory findings.…”
Section: Secondary Prevention Measures For Sars Have Involved Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall risk score was calculated by adding each component together. 21,22 The adequacy of the model was assessed by the c-statistic and diagnostic test. C-statistic is identical to the area under the receiver operating characteristic (ROC) curve for dichotomous outcomes.…”
Section: Methodsmentioning
confidence: 99%